High-Level synthesis assisted design and verification framework for automotive radar processors - Sikka, Prateek; Asati, Abhijit R; Shekhar, Chandra (Microprocessors and microsystems, 2020)
In radar-based advanced driver assistance systems, baseband processing is necessary to detect the speed, distance, and angle of elevation of the target (e.g., vehicle, pedestrian, traffic sign, etc.). The target and the source often move at high speeds; therefore, the computation rate must be sufficiently high to perform actions (e.g., braking) in real-time. Software-based implementations of such systems fall short of the required performance, which has led to an increase in the popularity of custom hardware implementations, e.g., on field-programmable gate arrays (FPGAs). FPGAs also serve as platforms to develop software concurrent with system-on-chip (SoC) development, thereby decreasing the time to market. High-level synthesis (HLS) tools are gaining considerable attention in the very-large-scale integration design community because of their flexibility. In this paper, we propose a novel design and verification framework for a RADAR processing SoC. The framework is assisted by an HLS-based design scheme for the processor and supports the application of a real-world stimulus to register transfer-level design implementation running on FPGAs. Customer use cases for the distance and velocity calculations are executed in a pre-silicon environment using range and Doppler processing on the Xilinx Kintex-7(XC 7K 480T) FPGA. Our findings show that the proposed framework, based on MATLAB HDL Coder and HDL Verifier, is superior to similar implementations from prior research in terms of speed and FPGA resources. This is owing to the usage of appropriate HLS directives and the usage of a novel design method based on application-specific bit width for intermediate data nodes.